Ti3C2Tx MXene decorated with Sb nanoparticles as anodes material for sodium-ion batteries. (4th February 2019) - Chen, Hong; Chen, Nan; Zhang, Meina; Li, Malin; Gao, Yu; Wang, Chunzhong; Chen, Gang; Du, Fei
Abstract: A large family of two-dimensional (2D) transition metal carbides, MXene, has demonstrated potential applications for electrochemical energy storage. 2D MXene sheets may buffer large volume changes and form a 3D conductive network to facilitate the electronic transfer of working electrodes. However, multilayer Ti3 C2 T x material could only deliver a moderate capacity in sodium ion battery cells, below the requirement of commercial applications. Herein, we decorated multilayer MXene (Ti3 C2 T x ) with Sb nanoparticles (NPs) via a facile solution-phase method, in which Sb NPs with a diameter of about 5–10 nm are absorbed on the surface of MXene layers by the electrostatic attraction action. The hybrid material Ti3 C2 T x @Sb-0.5 delivers a higher reversible capacity of 200 mA h g −1 at 0.1 A g −1 than that of pure Ti3 C2 T x (90 mA h g −1 ), and shows a much better capacity retention of nearly 98% after 500 cycles compared with Sb NPs. Also, it achieves superior rate performance (remaining a capacity of 127 mA h g −1 at 2 A g −1 ) and excellent long-term stability (a capacity retention of almost 92.3% after 8000 cycles). These results indicate that Ti3 C2 T x @Sb-0.5 possess a potential for high-performance sodium ion batteries anodes.